Risk Factors in Host and Environment for Cervicitis Among Commercial Sex Workers - Nazarwin Saputra; Bagoes Widjanarko; Henry Setyawan (Jurnal Kesehatan Masyarakat Andalas, 2016)
sexually transmitted infection (STI) remains a major health problem in some parts of the world. This study aimed to determine the host and environmental factors the effect on the incidence of cervicitis on sex workers. The study was observational case-control design with consecutive sampling technique. Risk factor for cervicitis is a history of sexually transmitted infections (p=0,0001), have couple (boy friend) different gender (p=0,014, OR=4,4; CI95%=1,3-14,3), history of oral sex/cunnilingus (p=0,003, OR=6,8;CI95%=1,9-24,8), smokers (p=0,0001, CI95%=5,6; CI95%=2,4-13,1). Condom use last sex behavior is a protective factor affecting the incidence of cervicitis (p=0,0001, OR= 0,198; CI95 %=0,07- 0,5). The conclusion of this study is to prevent servisitis at-risk groups of commercial sex workers it should avoid from exposure of agents that cause sexually transmitted infections, does not have a spouse who is not authorized (girlfriend) that leads to sex behavior, avoid behaviors oral sex / cunnilingus, no smoke. At-risk behavior should use condoms for prevention servisitis